View synthesis method for 3D video coding based on temporal and inter view correlation. Issue 11 (14th September 2018) - Tung, Long Vuong; Le Dinh, Minh; HoangVan, Xiem; Dinh, Trieu Duong; Vu, Tien Huu; Le, Ha Thanh
Abstract : Recently, in three‐dimensional (3D) television, the temporal correlation between consecutive frames of the intermediate view is used together with the inter‐view correlation to improve the quality of the synthesised view. However, most temporal methods are based on the motion vector fields (MVFs) calculated by the optical flow or block‐based motion estimation which has very high computational complexity. To alleviate this issue, the authors propose a temporal‐disparity‐based view synthesis (TDVS) method, which uses the MVFs extracted from the bitstreams of side views and motion warping technique to create the temporal correlation between views in the intermediate position. Then a motion compensation technique is used to create a temporal‐based view. Finally, the temporal‐based view is fused with a disparity‐based view which is generated by a traditional depth image‐based rendering technique to create the final synthesised view. The fusion of these views is performed based on the side information which is determined and encoded at the sender‐side of the 3D video system using a dynamic programming algorithm and rate‐distortion optimisation scheme. Experimental results show that the proposed method can achieve the synthesised view with appreciable improvements in comparison with the view synthesis reference software 1D fast (VSRS‐1D Fast) for several test sequences.